2016
DOI: 10.21273/hortsci.51.4.370
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Impacts Tomato Carotenoids, Soluble Sugars, and Organic Acids

Abstract: Plant growth regulators (PGRs) are chemicals used on a wide range of horticultural crops. These exogenous chemicals, similar to endogenous plant hormones, regulate plant development and stimulate a desired growth response, such as control of plant height. One such PGR is abscisic acid (ABA), which has been used effectively to improve fruit quality, specifically sugars and phytonutrients. The purpose of this study was to examine the effects of exogenous applications of ABA on tomato (Solanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
1
16
0
1
Order By: Relevance
“…A study conducted by Pérez-Jiménez et al [31] demonstrated the effect of ABA on mineral nutrient concentrations, soluble sugars, and yield of sweet pepper fruit. Previous research by de Freitas et al [52,53] and 48,51] on how ABA affects Ca concentrations, soluble sugar content, and yield in tomato plants presented opposing conclusions. For example, the work by Pérez-Jiménez et al [31] did not find differences in Ca and soluble sugar concentrations in sweet pepper fruit tissue.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A study conducted by Pérez-Jiménez et al [31] demonstrated the effect of ABA on mineral nutrient concentrations, soluble sugars, and yield of sweet pepper fruit. Previous research by de Freitas et al [52,53] and 48,51] on how ABA affects Ca concentrations, soluble sugar content, and yield in tomato plants presented opposing conclusions. For example, the work by Pérez-Jiménez et al [31] did not find differences in Ca and soluble sugar concentrations in sweet pepper fruit tissue.…”
Section: Discussionmentioning
confidence: 90%
“…In recent years, research has demonstrated how ABA influences plant metabolites, such as carotenoids [48,49], flavonoids [50], soluble sugars [49,51], and Ca uptake and distribution [12][13][14]52,53]. A study conducted by Pérez-Jiménez et al [31] demonstrated the effect of ABA on mineral nutrient concentrations, soluble sugars, and yield of sweet pepper fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, it was reported that ABA treatment mainly increased the β-carotene and lutein content in the leaves of tomato [20]. In the fruit tissue of tomato, the β-carotene content was also increased by ABA treatment [19]. Lutein and β-carotene contents were also higher in ABA-treated plants than in control plants in Chinese cabbage and turnip [29,30].…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the application of exogenous ABA has been shown to affect carotenoid content in Lycopersicon esculentum, as ABA treatment decreased the content of lutein but significantly increased the content of β-carotene. In two additional species of tomato, the application of ABA increased lutein, β-carotene and zeaxanthin in their leaves [19,20]. Correlated with the change in carotenoids, the expression of genes involved in the metabolic pathways of carotenoids was also influenced by ABA treatment.…”
Section: Introductionmentioning
confidence: 98%